Proposed Quality Plan for Shipbuilding in Indonesia Based on ISO 10005:2018 - Virliani, Putri; Rahadi, Shinta Johar Alif; Rina, Rina; Sari, Dian Purnama; Ismail, Abdi; Maruf, Buana; Bisri, Ahmad (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2023)
Ensuring quality is of utmost importance for the shipbuilding sector, as it involves addressing both the quality of processes and the final products to achieve efficient and cost-effective manufacturing. It has become a standard practice for shipyards to adopt certifiable management systems. ISO 9001:2015 sets out the necessary criteria for a Quality Plan, which is influenced by the company's overall quality policy and contractual obligations. In this context, ISO 10005:2018 offers guidance that can be utilized within the framework of quality plans to meet the specific requirements of a project. Several quality plans for Indonesian shipyards, only adopting ISO 9001 and ISO 10005:2018, have yet to be widely implemented. Thus, this paper adopts ISO 10005:2018 to identify the quality plan of three selected shipyards in Indonesia. The gap analysis technique is used to compare the current state of the quality plan with the desired conditions outlined in the ISO 10005:2018 standard. The identified gaps will determine the areas that require immediate attention and improvement in order to meet the requirements of ISO 10005:2018. The primary objective of this study is to facilitate the creation of a quality plan that adheres to the ISO 9001 and 10005 standards. Based on the comparison results of quality plans according to ISO 10005:2018 in shipyards A, B, and C, the recommendation is to integrate distinct clauses (6.4, 6.7.1, 6.7.3, 6.10, 6.13, and 6.15) to improve the quality plans across these specific shipyards.